Effect of platelet rich fibrin on stability of dental implants: A systematic review and meta-analysis - Shaheda Tabassum; Raj, Subash Chandra; Rath, Hemamalini; Mishra, Asit Kumar; Mohapatra, Annuroopa; Kaushik Patnaik (International Journal of Health Sciences, 2022)
Objective: The aim of the study is to provide a systematic review of the potential evidence for the effect of platelet rich fibrin (PRF) on stability of dental implants. Methods: A systematic review was performed based on the Preferred Reporting Items for Systematic review and Meta-analysis. An extensive and comprehensive electronic search was carried out from January 2000 to March 2021, independently by author in PUBMED, Cochrane Central Register of Controlled Trials, Google Scholar, Scopus, Embase, and Web of Science irrespective of publication status, date, or language. For any registered ongoing or completed but unpublished trial, ClinicalTrials.gov, World Health Organization International Clinical Trials Registry Platform, and Cochrane Oral Health’s Trials Register websites were searched. Randomized, controlled, and clinical trials which assessed the stability of implant with and without use of PRF using Osstell device by radiofrequency analysis were selected. Results: The electronic and manual search yielded 630 studies. In all the eight included studies implant stability was measured using same ISQ units by Osstell device. Meta-analysis was carried out in six studies that had similar comparisons and reported the same outcomes at same time interval. Random effect models have shown pooled mean difference of 4.49 (95% CI 1.22–7.76) for 1-week post-insertion, 3.65 (95% CI 2.21–5.09) for 4-week post insertion, 3.25 (95% CI 0.03–6.47) for 8-week post-insertion, and 2.79 with 95% CI of 0.48, 5.10 for 12-week post-insertion. Conclusions: The present systematic review suggests that PRF is effective in improving secondary implant stability with certain limitations and displays possible implication for clinical practice.